Improving instructional practice through peer observation and feedback: A review of the literature - Brady L. Ridge; Alyson L. Lavigne (Arizona State University, 2020)
The Every Student Succeeds Act provides an opportunity for policymakers and researchers to revisit what is known about effective teacher evaluation practices to make better-informed decisions moving forward. Principals-responsible for implementing new teacher evaluation reforms and accommodating the demands to spend more time observing and providing feedback to teachers-are overworked. They have little time to provide high-quality feedback, and may lack important content-based expertise. With these considerations in mind, we explore the role of peer observation and feedback as a vehicle to move beyond high-stakes evaluation and re-center efforts on instructional improvement. Our systematic review of extant literature (n = 38 documents, 92% peer-reviewed empirical articles) indicates that peer observation and feedback is a promising practice for instructional improvement, but one that lacks sufficient evidence. Policy, thus, can encourage innovation and research around this practice so that peer observation and feedback models can be piloted and the most effective established, as well as strategies to tackle the biggest barriers schools, particularly U.S. schools face in implementing such a practice-time.